Analisis Nilai Tambah Produk Keripik Salak Menggunakan Metode Hayami - Chrestiana Aponno; Septina Louisa Siahaya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to find out how much adeed value is obtained from the processing of salak furit into salak chips carried out by Sumalow community group in Masohi City, Central Maluku Regency. The results of this research are expected to provide information for community groups that manage this business, to create new strategies that can develop the income and welfare of the local community. The analysis technique used the Hayami method bay looking at processing of salak chips for one production cycle in April 2023. The results showed that business of processing salak fruit into salak chips has an added value of Rp. 2.700 per kg with a value added ratio of 32 % which is the medium ratio indicator in the range of 15 – 40 %. This means there is a relatively moderate increase in added value for processing of salak fruit into salak chips. This ratio can be increased if Dusun Simalow community group as business manager can increase their productivity, especially labor productivity and production equipment productivity also supported by an increase in profitable market share. In addition to increasing added value, it is hoped that it will also encourage an increase in welfare of the Simalow Hamlet Community.